PENGARUH TUNJANGAN KINERJA TERHADAP MOTIVASI KERJA, DISIPLIN KERJA DAN KINERJA PEGAWAI BALAI PENGELOLAAN DAERAH ALIRAN SUNGAI DI JAWA TIMUR - Hanifah, Yusnia (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The purpose of this study was to analyze the influence of performance allowance on motivation, discipline, and employee performance in the Watershed Management Center (BPDAS) in East Java Province. The sample consisted of 83 (eighty three) employees of BPDAS. Data were analyzed using path analysis. Results show that: (1) performance allowance has no significant influence on work motivation, (2) performance allowance has no significant influence on work discipline, (3) performance allowance has a significant negative influence on employee performance, (4) work motivation has no significant influence on employee performance, and (5) work discipline has no significant influence on employee performance. The fact that the existing performance allowance has no influence on motivation, discipline, and employee performance urges the system improvement. Keywords: Work Allowance, Motivation, Discipline, Performance.